2018
DOI: 10.5455/medarh.2018.72.292-294
|View full text |Cite
|
Sign up to set email alerts
|

Holt-Oram Syndrome in a Patient with Crohn's Disease: a Rare Case Report and Literature Review

Abstract: Introduction:Holt-Oram syndrome (HOS) is an uncommon autosomal dominant disorder defined by congenital cardiac defects, some anatomical deformities in the upper limb and conduction abnormalities. Sequence alteration of TBX5 gene located on chromosome 12 has associated with HOS.Case report:We present the case of a 26-year-old female with known upper limb alteration and ventricular septal defect who later in life developed Crohn’s disease.Conclusion:To the best of our knowledge association of Holt-Oram syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
0
0
2
Order By: Relevance
“…2 Multisystem involvement is seldom reported. 7 A large prospective study including 1653 patients with upper limb malformations (clinically diagnosed as Heart-hand syndrome) by Yin et al showed that 11 % had echocardiographic and 1% had electrocardiographic abnormalities, the commonest being the atrial septal defect (38%) followed by tricuspid regurgitation (37%), ventricular septal defect (6%). 8 Conduction abnormalities were present only in 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multisystem involvement is seldom reported. 7 A large prospective study including 1653 patients with upper limb malformations (clinically diagnosed as Heart-hand syndrome) by Yin et al showed that 11 % had echocardiographic and 1% had electrocardiographic abnormalities, the commonest being the atrial septal defect (38%) followed by tricuspid regurgitation (37%), ventricular septal defect (6%). 8 Conduction abnormalities were present only in 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…К наиболее распространенными дефектам перегородок сердца относятся такие, как ДМПП (44,4%) и дефект межжелудочковой перегородки (29,4%) [1]. Имеются также сообщения о более тяжелых пороках: атриовентрикулярный канал, тетрада Фалло, синдром гипоплазии левых отделов сердца и коарктация аорты [5]. В основном данные пороки существуют в изолированном виде и крайне редко возникает их комбинация.…”
Section: Discussionunclassified
“…Трудность лечения пациентов с синдромом Холта-Орама зависит от структурных нарушений РОССИЙСКИЙ ВЕСТНИК ПЕРИНАТОЛОГИИ И ПЕДИАТРИИ, 2020; 65: (5) ROSSIYSKIY VESTNIK PERINATOLOGII I PEDIATRII, 2020; 65: (5) КЛИНИЧЕСКИЕ СЛУЧАИ сердца [8]. В нашем случае трудность оперативного вмешательства была связана с наличием множественных дефектов межжелудочковой перегородки по типу швейцарского сыра и стеноза аортального клапана.…”
Section: Discussionunclassified